2022
DOI: 10.1017/s0029665122000994
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to tackling emotional loss of control of eating across the weight spectrum

Abstract: Emotional overeating is a process that is particularly relevant to people within the binge spectrum of eating disorders. Approximately a third of people with overweight share this phenotype. In addition, this behaviour may occur in neurodevelopmental disorders (attention-deficit hyperactivity disorder (ADHD)) and other psychiatric disorders. The biopsychosocial underpinnings of emotional eating include a genetic vulnerability to a higher weight and various cognitive and emotional traits. The environment also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Binge eating was triggered by food cues or cues that could become related to negative affect in the model over the course of BN and BED (Chami et al, 2020). Novel treatments that target the components of the maintenance mechanisms are in development (Treasure et al, 2022) and showed improvements in inhibitory control (Chami et al, 2020; Keeler et al, 2022). However, CBT targeting multifactorial processes in the model remains untested in patients with BN and BED.…”
Section: Introductionmentioning
confidence: 99%
“…Binge eating was triggered by food cues or cues that could become related to negative affect in the model over the course of BN and BED (Chami et al, 2020). Novel treatments that target the components of the maintenance mechanisms are in development (Treasure et al, 2022) and showed improvements in inhibitory control (Chami et al, 2020; Keeler et al, 2022). However, CBT targeting multifactorial processes in the model remains untested in patients with BN and BED.…”
Section: Introductionmentioning
confidence: 99%